Perbandingan Pembiayaan Sekolah Tinggi di Indonesia dengan Negara Timur Tengah dan Dampaknya terhadap Keberhasilan Pendidikan - Silvina, Dini; Gep Rianto; Ananda Dilonia; Aqbil Daffa Siahaan; Aprizal Ahmad (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the comparison of higher education financing models between Indonesia and several Middle Eastern countries, aiming to understand their impact on educational success. The research employs a qualitative approach, analyzing government budgets, funding mechanisms, and educational outcomes documented in recent reports. Findings indicate significant differences in financing structures, with Middle Eastern countries often allocating higher per-student funding and implementing more diverse financial support systems such as scholarships and public-private partnerships. In contrast, Indonesia faces challenges in equitable fund distribution despite increasing budget allocations. The study reveals that effective financing positively correlates with improved educational infrastructure, faculty quality, and student performance. The implications highlight the need for Indonesia to enhance funding strategies by adopting best practices observed in the Middle East to achieve sustainable educational development and greater academic achievement.